THE EFFECT OF USING VIDEO ON STUDENTS’ LISTENING SKILL AT SMP WAHID HASYIM MALANG - Sabila Yassaroh (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: The study aimed to investigate the effect of using video on students’ listening skill at SMP Wahid Hasyim Malang. The research design of this study is a Quasy-experimental research in form of pre-test and post-test. There were 44 junior high school students involved as the participants in this research. The participants were classified into two group as control group and experimental group. The researcher divided two group in which class VIIA as the control group and VIIC as the experimental group. The result of the study showed that count<t table (2,852 <2,423) and p <0.05(p = 0.05<0.05). That means the H0 was accepted, HI was rejected because, there were no significant effect in using video to increase students listening comprehension skill. It was proved that using video was not the proper media to increase students’ listening comprehension skill. Key Words: Listening skill, video, effect